Scanning Electron Microcopy Analysis after Electrical Discharge Machining of Advanced Ni-Based Alloy - Anand Pandey; Ashish Goyal; Ranjan Walia; Varun Jurwall (Engineering Proceedings)
Electrical discharge machining (EDM) and its variant methods are used to fabricate three-dimensional and complex geometrical features from micro level to nano dimensions. Researchers have successfully experimented with high-strength alloys and composite materials, finding wide applications in defense, automobile, and medical industries to shape precision micro-grooves (straight, tapered, and angular-based). Motion-type EDM methods (when the tool electrode is moving) utilize capabilities to rotate the tool electrode or work material to manufacture grooves (applications included in the micro-electronics sector, aircraft engines, and diffraction gratings). In the present investigation, experimental studies were performed to fabricate the grooves of high-strength NI-based alloy using the EDM electrode (cylindrical in shape) using Taguchi’s L-18 orthogonal array. SEM studies were performed at different magnifications to check and analyze the recast layer formation on the surface of the groove at different parametric settings. The analysis of the effect of input parameters was tested on machine performance responses viz. MRR, EWR, and surface roughness. This was revealed, and the optimum levels of process parameters were analyzed, showing the best surface finish with a maximum metal removal rate after analyzing using SEM. The MRR was found to increase with an increase in the thickness of the disk electrode (0.1–0.6) at all parametric settings. Also, roughness increased with an increase in the current settings from 6 to 12 A. SEM analysis depicts that groove thick ness at the bottom (565 µm) and top of the groove (1.14 mm).